Molecular Characterization and Phylogeny of Novel Diverse Nitrogen Fixing Microsymbionts Associated with Vachellia (Acacia) leucophloea in Arid and Semi Arid Regions of Rajasthan - Choudhary, Sunil; Meghwal, Raju R.; Sankhla, Indu S.; Tak, Nisha; Gehlot, Hukam S. (Indian Forester, 2017)
A total of 57 bacterial strains were isolated and purified from root nodules of Vachellia (Acacia) leucophloea growing in soils of different districts of Western Rajasthan. These strains were characterized on the phenotypic and molecular basis. Their carbon utilization and intrinsic antibiotic resistance patterns were different from the closely related type strains. Genetic diversity assessed through PCR-RFLP and RAPD profiles. On the basis of 16S rDNA sequencing four isolates (AL5, 19, 48 and AL53) were identified as strains of Ensifer sp., while AL39 and AL11 as strains of Bradyrhizobium sp. and Mesorhizobium sp. respectively. The phylogentic tree based on 16S rRNA gene sequences suggests that all these strains are novel and different from the existing type strains of Ensifer and Bradyrhizobium. The symbiotic genes nodA and nifH were sequenced for strain AL5 (Ensifer sp.) and AL39 (Bradyrhizoibium sp.). Symbiotic gene phylogeny for Bradyrhizobium strains was found congruence with the species phylogeny while in case of Ensifer strains it was found incongruent with species phylogeny. Host range analysis suggests that some of the strains were promiscuous and nodulate other members of the genus Acaciaand Prosopis. Thus such strains are useful in developing healthy nurseries of forest trees in the arid regions of Rajasthan.